PCN87 Economic Evaluation of Sunitinib as First-Line Treatment for Metastatic Renal Cell Carcinoma in Colombia (2016)
To estimate the cost-effectiveness of sunitinib as first-line treatment for metastatic renal-cell carcinoma (mRCC) from the Colombian health system perspective.